Comparative effects of unilateral and bilateral bone conduction hearing devices on functional hearing and sound localization abilities in patients with bilateral microtia-atresia. (2nd July 2020) - Fan, Xinmiao; Ping, Lu; Yang, Tengyu; Niu, Xiaomin; Chen, Yushan; Xia, Xin; Gao, Ruzhen; Fan, Yue; Chen, Xiaowei
Abstract: Background: Various amplification options are available for patients with congenital bilateral conductive hearing loss. Unilateral bone conduction hearing device (BCHD) is widely used for these patients, whereas benefits of bilateral BCHDs in certain subgroups of patients require further exploration. Objectives: To evaluate functional and directional hearing in patients with unilateral Bonebridge (MEDEL) and contralateral ADHEAR (MEDEL) devices. Materials and methods: This study included 32 patients (20 males, 12 females), of mean age 11.8 years (range 7–27 years). Hearing thresholds, speech perception and sound localization were tested three months after activation of the Bonebridge under three conditions: unaided, unilateral BHCD (Bonebridge) and bilateral BHCDs (Bonebridge plus contralateral ADHEAR). Patient acceptance of these devices in daily life was evaluated by questionnaire. Results: Compared with unaided, the mean hearing thresholds (0.5, 1, 2, and 4 kHz) and speech perception with unilateral BCHD and bilateral BCHDs were improved significantly ( p  < .05 each). Markers of directional hearing ability, including percentages of accurate responses, bias angles and RMS errors, were significantly better with bilateral BCHDs than unilateral BHCD ( p  < .05 each). Questionnaire revealed high patient satisfaction with both unilateral and bilateral devices. Conclusions: Functional hearing and sound localization abilities were better with bilateral BCHDs than unilateral BCHD.